More than half a century of evolutionary studies in Rhodnius prolixus Stål, 1859 (Hemiptera, Triatominae): revisiting and discussing old and new data on intra- and interspecific reproductive barriers - Kaio Cesar Chaboli Alevi; Amanda Ravazi; Jader de Oliveira; Yago Visinho dos Reis; Isadora de Freitas Bittinelli; Luiza Maria Grzyb Delgado; Jociel Klleyton Santos Santana; Maria Tercília Vilela de Azeredo-Oliveira; João Aristeu da Rosa; Mauro Toledo Marrelli; Cleber Galvão (PLoS ONE, 2025)
Rhodnius represents a paraphyletic group, being R. prolixus one of the most important domestic vectors of the Chagas disease. Several phenotypic identification problems, as well as divergences between classical and molecular taxonomy, have been reported. Furthermore, phylogenetic and phylogenomic studies demonstrated possible introgression events between R. prolixus and R. robustus . Based on the above, we revisited all the literature on hybridization involving R. prolixus and performed interspecific crosses between R. prolixus and other species of the R. prolixus group ( R. nasutus , R. neivai , and R. robustus ) to evaluate potential reproductive barriers and discuss taxonomic and evolutionary issues related to intra- and interspecific reproductive isolation. With the exception of the cross between R. prolixus females and R. neivai males, all other combinations resulted in hybrid offspring. Moreover, except for the cross between R. prolixus females and R. robustus males, all other combinations exhibited postzygotic barriers, including inviability, sterility and/or hybrid collapse. These results indicate that, in at least one direction, R. nasutus , R. neivai , and R. robustus are reproductively isolated from R. prolixus , confirming the specific status of the four taxa. Furthermore, based on the observed barriers, we suggest that introgression is unlikely between R. prolixus and R. nasutus , unlike R. neivai and R. robustus , which could exchange genetic material with R. prolixus through introgression, under natural conditions. Finally, we discuss all available literature on intra- and interspecific crosses of R. prolixus , demonstrating that R. pictipes and R. neglectus are also reproductively isolated from R. prolixus . Additionally, we highlight reproductive barriers observed between allopatric populations of R. prolixus , emphasizing the need for a phylogenomic study – including field-collected specimens sampled across the entire distribution of R. prolixus – to clarify evolutionary and taxonomic questions.